PENGARUH AKTIVA TETAP DAN AKTIVA LANCAR TERHADAP PENDAPATAN PADA SIMPAN PINJAM PEREMPUAN UPK GERBANG SARI KECAMATAN RENGAT BARAT - Hapsila, Angga (JURNAL MANAJEMEN DAN BISNIS, 2018)
This research is about savings and loans for women UPK Gerbang Sari, Rengat Barat District. The research lasted for 5 (five) months. This research try to determine the effect of whether there was a significant influence between fixed assets and current assets on income on women's savings and loans UPK Gerbang Sari, Rengat Barat District. The formulation of the problem to be investigated is whether there is a simultaneous and partial effect between fixed assets and current assets on women's savings and loan income UPK Gerbang Sari, Rengat Barat District. This research used quantitative methods, that illustrates whether there is a significant influence between fixed assets and current assets on income on savings and loans for women UPK Gerbang Sari, Rengat Barat District. To analyzed the data, this research used multiple regression, correlation coefficients, and Hypothesis testing which will be assisted using SPSS version 21. From the results of the study with the regression equation Y = 1,379,231-1,075 X1 + 0,214X2. This means: a = if the fixed assets and current assets are equal to Zero (0), then the value of income is equal to 1,379,231. The coefficient of multiple correlation R is 0.686. and furthermore tested with multiple determination Keofisie (R2 is 0.471. This indicates that (X1) fixed assets and (X2) current assets have together an influence of 47.10% and the remaining 52.90% is influenced by variables other than ( X1) and (X2). Hypothesis testing in which F arithmetic (0.891) <Ftable (3.00), then there is no significant effect simultaneously between fixed assets and current assets to income on savings and loans for women in UPK Gerbang Sari, Rengat Barat District.